(untitled) (International Journal of Management and Sustainability, 2022)
Quantitative results derived by Extended Ordered Probit Model on 91 SMEs in Soc Trang province show the influential role of innovation and entrepreneurial orientation on the sales growth of enterprises. These two factors confirm their association is indispensable in the development of enterprises. In addition, the results also provide information on the significant contribution of endogenous variables in the model. Of which the application of information technology (IT) in the organizational administration is endogenous and contributes significantly to innovation and entrepreneurial orientation on SMEs performance, which the older SMEs are, the more interested they are in applying IT in the organizational administration. The finding is an important message for local SMEs who need to rethink the application of IT systems to corporate governance. It is also very useful reference information for local policymakers to create an approach that supports SMEs in developing innovation strategies and entrepreneurial orientation toward market integration.